Digital Business Accounting in Streaming Platforms: Narrative Disclosure, Content Cost Efficiency, and Financial Performance of iQIYI 2020–2024 - Hana Dhayan; Erwin Febriansyah; Maulidia Akhir (Community Engagement and Emergence Journal (CEEJ), 2026)
This study examines the relationship between narrative disclosure, content cost efficiency, and financial performance in a digital streaming platform. Using iQIYI, Inc. as a longitudinal case from 2020 to 2024, this study applies a quantitative content analysis of five Form 20-F annual reports and non-parametric correlation tests. A Composite Content Analysis Index (CA_INDEX) is developed from four disclosure dimensions: drama-related content frequency, content strategy orientation, subscriber discourse, and management tone. Financial performance is measured using net income, gross profit, content cost, content cost ratio, membership revenue, and gross margin. The results show that content strategy orientation and management tone are positively associated with profitability, while CA_INDEX is negatively associated with content cost. These findings indicate that digital platform performance is not merely driven by higher content spending, but by more efficient resource allocation and clearer strategic disclosure. This study contributes to digital business accounting literature by showing how narrative disclosure and intangible content investment efficiency can provide relevant information for assessing financial performance in platform-based companies.